2004
DOI: 10.1007/bf02256095
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbyl palmitate augments hypoxic respiratory response in the cat

Abstract: The redox signaling is germane for the hypoxia-sensing mechanisms at the carotid body. This raises the strong possibility that agents possess reducing and antioxidant attributes, such as ascorbate, could influence the hypoxic respiratory response. However, water solubility of ascorbate makes its effectiveness at membrane-associated target sites dubious. In this study, we sought to determine the effect of ascorbyl-6-palmitate (AP), a lipid-soluble derivative of ascorbate which penetrates biomembranes, on hypoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Further evidence suggesting that vitamin C may play a critical role in oxygen sensing and augmenting the responses to hypoxia has been shown in a recent study of ascorbyl palmitate in hypoxic cats. 8 Ascorbyl palmitate is a lipid-soluble derivative of vitamin C; its lipid solubility increases its availability to chemoreceptors in the carotid body. The study showed modification of the ventilatory response to hypoxia and concluded that ascorbyl palmitate may have therapeutic effects in hypoxia.…”
Section: To the Editormentioning
confidence: 99%
“…Further evidence suggesting that vitamin C may play a critical role in oxygen sensing and augmenting the responses to hypoxia has been shown in a recent study of ascorbyl palmitate in hypoxic cats. 8 Ascorbyl palmitate is a lipid-soluble derivative of vitamin C; its lipid solubility increases its availability to chemoreceptors in the carotid body. The study showed modification of the ventilatory response to hypoxia and concluded that ascorbyl palmitate may have therapeutic effects in hypoxia.…”
Section: To the Editormentioning
confidence: 99%